Almond as Alternative Media for Growth of Staphylococcus aureus and Escherichia coli - Nurmalasari, Ary; Marlina, Leni; Ruhimat, Undang; Mutmainah, Rahayu Nirmatul (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
The high cost of media for microbial culture encourages researchers to create alternative media using local raw materials at low prices. One of the most important media compositions for bacterial growth is protein. This content can be obtained from nuts, one of which is almonds (Prunus dulcis). The purpose of this study   is   to  find  natural   media  that    has   the   potential    for   the    growth of microorganisms at a low price. The  research method  used is an experimental method to determine the growth of Escherichia coli and Staphylococcus aureus bacteria on natural media of almonds. The results showed the growth of Escherichia coli and Staphylococcus aureus bacteria in this alternative media of almonds. Based on the results of the study, it can be concluded that  almond  nut  media  can  be  applied  as  an  alternative  medium in   laboratory research, especially in the field of_microbiology. It is suggested that further research should be carried out on natural media which are sources of carbohydrates and proteins as alternative growth media for bacteria.